2004
DOI: 10.1007/s00198-003-1568-z
|View full text |Cite
|
Sign up to set email alerts
|

Hip fracture risk in statin users?a population-based Danish case-control study

Abstract: Based on animal studies, statins (3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors) have been suggested as potential agents in the treatment of osteoporosis. In some epidemiological studies, statins have been associated with a reduced fracture risk. Our objective was to examine associations between statin treatment and risk of hip fracture in a population-based case-control study. A total of 6660 subjects with hip fracture and 33,274 gender- and age-matched population controls were identified from 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 30 publications
3
57
0
2
Order By: Relevance
“…Since Mundy et al [31] published their report on the stimulatory effects of statins on bone formation, numerous clinical studies have evaluated the beneficial effects of statins on BMD [32], fracture risk [32,33] and bone metabolism [26,[34][35][36][37][38]. It remains obscure, however, whether the clinical use of statins has beneficial effects on bone health as well [26], even though their numerous pleiotropic effects are well known.…”
Section: Discussionmentioning
confidence: 99%
“…Since Mundy et al [31] published their report on the stimulatory effects of statins on bone formation, numerous clinical studies have evaluated the beneficial effects of statins on BMD [32], fracture risk [32,33] and bone metabolism [26,[34][35][36][37][38]. It remains obscure, however, whether the clinical use of statins has beneficial effects on bone health as well [26], even though their numerous pleiotropic effects are well known.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some clinical studies reported higher bone mineral density (BMD) (17) and lower fracture rates (17,20) in patients treated with statins, but others did not (8,13,21,22). One of the possible reasons for these discrepancies among these clinical studies might be the difference in the statin used (4,5,7,14,23), as some investigators have suggested that its beneficial effects on bone were found only in lipophilic statins, but not hydrophilic ones (4,5,23 (Fig.…”
Section: Although the 3-hydroxy-3-methylglutaryl Coenzyme A (Hmg-coa)mentioning
confidence: 90%
“…Several classes of medications are known to decrease bone mass: glucocorticoids (e.g., for treatment of autoimmune disorders) [75,77], lithium [78], and anti-convulsants [79]. Other medications are known to increase bone mass: estrogen (e.g., postmenopausal hormone replacement therapy) [80], statins [81], and thiazide diuretics [81].…”
Section: Medication Usementioning
confidence: 99%